Efficacy and safety of secukinumab in patients with spondyloarthritis and enthesitis at the Achilles tendon: results from a phase 3b trial. (3rd November 2021) - Behrens, Frank; Sewerin, Philipp; de Miguel, Eugenio; Patel, Yusuf; Batalov, Anastas; Dokoupilova, Eva; Kleinmond, Christine; Pournara, Effie; Shekhawat, Ankita; Jentzsch, Claudia; Wiedon, Annette; Baraliakos, Xenofon; et al.
Abstract: Objective: ACHILLES aimed to demonstrate efficacy of secukinumab on Achilles' tendon enthesitis in spondyloarthritis (SpA) patients. Methods: Patients ≥18 years ( n  = 204) with active PsA or axial SpA and heel enthesitis were randomized 1:1 to secukinumab 150/300 mg or placebo up to week 24, and thereafter placebo patients were switched to secukinumab. Results: At week 24, a higher, yet statistically non-significant ( P  = 0.136), proportion of patients in secukinumab vs placebo reported resolution of Achilles tendon enthesitis in affected foot (42.2% vs 31.4%; odds ratio [OR] = 1.63; 95% CI: 0.87, 3.08). Proportion of patients reporting resolution of enthesitis based on Leeds Enthesitis Index was higher with secukinumab vs placebo (33.3% vs 23.5%; OR = 1.65; 95% CI: 0.85, 3.25) at week 24. Mean change from baseline in heel pain at week 24 was higher in secukinumab patients vs placebo (−2.8 [3.0] vs −1.9 [2.7]). Greater improvements with secukinumab were observed in heel enthesopathy activity and global assessment of disease activity. Imaging evaluation by local reading confirmed heel enthesitis on MRI at screening for all patients. Based on central reading, 56% presented with bone marrow oedema and/or tendinitis; according to Heel Enthesitis MRI Scoring System (HEMRIS) post hoc analysis, 76% had signs of entheseal inflammation while 86% had entheseal inflammation and/or structural changes. Conclusion: A substantial proportion of patients showed no signs of inflammation on the centrally read MRIs despite a clinical diagnosis of heel enthesitis, thus highlighting that the discrepancy between the clinical and imaging assessments of enthesitis requires further investigation. Although ACHILLES did not meet the primary end point, the study reported clinically meaningful improvements in patient-related outcomes. Trial registration: clinicaltrials.gov, NCT02771210